Polemik Keabsahan Naskh Intra-Qur’an dan Ekstra-Qur’an - Sa'dullah Sa'dullah (Islamic Religious Education Departement, 2022)
The Polemic of the Validity of Intra-Qur'an and Extra-Qur'an Texts. Islamic Education Department, Faculty of Social Sciences, Jakarta State University. Two texts are polemic in this discussion, namely intra-Qur'anic texts (deletion between verses) and extra Qur'anic texts (deletion of the Koran on previous holy books and religions). The naskh polemic occurred because of the uncertainty about whether any verses of the Qur'an were in the text, some acknowledged. Still, others rejected, for various reasons, the mansukh of the poetry of the Qur'an. The term naskh, which means